El agroturismo y el desarrollo rural de la parroquia Antonio Sotomayor del cantón Vinces, provincia de los Ríos - Añi España, Romario Antonio (2017)
Chapter I details the idea or topic of research, defined as the existing problem for the determination of the variables to study, details how it is carried out at national, local and international level, then defines the approach of the problem that it is derived from the general and specific problem, as well as the objectives obtained through the problematization matrix, in the same way it raises the reason for the study as the justification is called. In chapter II the theoretical and conceptual foundations referring to agrotourism and rural development, cited in a precise way with the corresponding authors in terms of their conceptualization, are also reflected, as well as detailing the investigative background on the basis of this research as support for the generation of the proposal. Chapter III mentions the applied statistical tests and the results of the research using the techniques applied with the respective analysis and interpretation of the data, for the collection of the information that justifies the executed investigation, resulting in the conclusions and recommendations contributing to the generation of the present proposal. Chapter IV details the proposal according to the results obtained, defining its scope and what it is desired to achieve. In addition, the background of the same is described through the application of similar projects implemented justifying the reason for its application and the benefits and beneficiaries, as well as the objectives thereof and finally the components described in steps for the achievement of the proposal are established.